2020
DOI: 10.1507/endocrj.ej19-0389
|View full text |Cite
|
Sign up to set email alerts
|

Anagliptin suppresses diet-induced obesity through enhancing leptin sensitivity and ameliorating hyperphagia in high-fat high-sucrose diet fed mice

Abstract: Obesity is a major risk factors for type 2 diabetes, and weight loss is beneficial to diabetic patients who are obese or overweight. Dipeptidyl peptidase-4 (DPP-4) inhibitors are anti-diabetic drugs. Although it has been known that the effect of most of the DPP-4 inhibitors on body weight is neutral, several studies suggested that some DPP-4 inhibitors suppressed body weight. Nonetheless, the mechanisms underlying DPP-4 inhibitor-induced weight loss are not fully understood. In this study, the mice fed high-fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Recent research has shown that high-calorie diets can cause hyperphagia and promote obesity. Feeding obese mice with 2-fucosyllactose and anagliptin reduced both body weight and dietary intake (Kohno et al, 2020;Lee et al, 2020). We did observe increased body weights in mice fed a high-calorie diet, and reduced food consumption after PC gavage in obese mice, but PC administration did not reduce mouse body weight, illustrating that weight loss was not an effect of PC administration.…”
Section: Discussionmentioning
confidence: 62%
“…Recent research has shown that high-calorie diets can cause hyperphagia and promote obesity. Feeding obese mice with 2-fucosyllactose and anagliptin reduced both body weight and dietary intake (Kohno et al, 2020;Lee et al, 2020). We did observe increased body weights in mice fed a high-calorie diet, and reduced food consumption after PC gavage in obese mice, but PC administration did not reduce mouse body weight, illustrating that weight loss was not an effect of PC administration.…”
Section: Discussionmentioning
confidence: 62%
“…The molecular structure of anagliptin is shown in Figure . Anagliptin has shown promising antidiabetic properties in both clinical trials and animal experiments. , Recently, it was reported that the cytotoxicity and apoptosis induced by endogenous amyloid β in the neurons could be alleviated by anagliptin . Pronounced antioxidative stress effects have also been reported during the treatment of type II diabetes with anagliptin .…”
Section: Introductionmentioning
confidence: 99%
“…Although the cardiovascular safety of DPP-4 inhibitors has been proven in T2DM, the net effect of these drugs on leptin concentrations in obesity-related disease remains unclear [24]. In Kitamura's study, leptin sensitivity was enhanced after anagliptin treatment in high-fat diet fed mice [25]. In the study evaluating the inhibitory effect of vildagliptin on brosis markers on white adipose tissue of high-fat diet-induced obese mice, vildagliptin prevents the increase of brosis markers and reduces leptin levels [26].…”
Section: Discussionmentioning
confidence: 99%